Proteomic analysis reveals the roles of silicon in mitigating glyphosate-induced toxicity in Brassica napus L. - Probir Kumar Mittra; Md Atikur Rahman; Swapan Kumar Roy; Soo-Jeong Kwon; Abhik Mojumdar; Sung Ho Yun; Kun Cho; Seong-Woo Cho; Meiliang Zhou; Tomoyuki Katsube-Tanaka; Sun-Hee Woo (Scientific Reports)
Abstract Glyphosate (Gly) is a widely used herbicide for weed control in agriculture, but it can also adversely affect crops by impairing growth, reducing yield, and disrupting nutrient uptake, while inducing toxicity. Therefore, adopting integrated eco-friendly approaches and understanding the mechanisms of glyphosate tolerance in plants is crucial, as these areas remain underexplored. This study provides proteome insights into Si-mediated improvement of Gly-toxicity tolerance in Brassica napus. The proteome analysis identified a total of 4,407 proteins, of which 594 were differentially abundant, including 208 up-regulated and 386 down-regulated proteins. These proteins are associated with diverse biological processes in B. napus, including energy metabolism, antioxidant activity, signal transduction, photosynthesis, sulfur assimilation, cell wall functions, herbicide tolerance, and plant development. Protein-protein interactome analyses confirmed the involvement of six key proteins, including L-ascorbate peroxidase, superoxide dismutase, glutaredoxin-C2, peroxidase, glutathione peroxidase (GPX) 2, and peptide methionine sulfoxide reductase A3 which involved in antioxidant activity, sulfur assimilation, and herbicide tolerance, contributing to the resilience of B. napus against Gly toxicity. The proteomics insights into Si-mediated Gly-toxicity mitigation is an eco-friendly approach, and alteration of key molecular processes opens a new perspective of multi-omics-assisted B. napus breeding for enhancing herbicide resistant oilseed crop production.